Pediatric facial trauma management: Emergency case in a toddler - Rarasati, Swarantika Aulia; Sylvyana, Melita; Putri, Dian Maifara (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2024)
Background: Facial soft tissue trauma cases are often encountered in the emergency room. Soft tissue trauma, especially to the face, is rarely life threatening. It varies in shape, size, and depth and can also affect surrounding organs. The treatment of soft tissue trauma can be complicated and may have a significant impact on facial function and, especially, facial aesthetics. Children are easily injured due to their active nature. Soft tissue trauma to the faces of toddlers is challenging even for experienced surgeons; however, wound debridement and suture management under general anesthesia should be considered. Purpose: The aim of this article is to deliver a thorough overview of the evaluation and treatment of soft tissue injuries in children, covering initial assessments, physical examinations, the application of antimicrobial therapies, and preparation for surgical procedures. Case: An 11-month-old girl went to the emergency department of Hasan Sadikin General Hospital, Bandung, with injuries to her left cheek and upper left lip sustained when she fell, and her face hit the edge of a cement pot at home. There was no history of unconsciousness, nausea and vomiting. The injury was diagnosed as vulnus laceratum of the left face and upper lip region. Case management: Emergency management was carried out by triage, Tetagam injection, and early wound debridement and suture under general anesthesia because the patient was uncooperative. Wounds on the face and lips were primary sutured layer by layer, returning the wound edges to their normal anatomical position. Conclusion: The management of facial soft tissue injuries in toddlers requires general anesthesia for adequate and accurate wound debridement and suture, so that functional and aesthetic effects can be satisfactorily obtained.